2020
DOI: 10.1097/hpc.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Administration in Patients With COVID-19 Shock

Abstract: Purpose: To understand the hemodynamic effect of angiotensin II as a vasopressor in patients with shock secondary to COVID-19 infection. Methods: A retrospective analysis was performed on all patients at a single center with COVID-19 infection and shock who were treated with angiotensin II. The hemodynamic response to angiotensin II was estimated by recording the mean arterial pressure, norepinephrine equivalent dose (NED) and urine output. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…patients who did not receive vasopressors [20-37,39-48,50,52]. Moreover, three studies included patients who received angiotensin-II [38,49,51] and, out of those, two compared the use of angiotensin-II with other vasopressors [49,51] (Appendix C2). Table 1 summarizes the main characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…patients who did not receive vasopressors [20-37,39-48,50,52]. Moreover, three studies included patients who received angiotensin-II [38,49,51] and, out of those, two compared the use of angiotensin-II with other vasopressors [49,51] (Appendix C2). Table 1 summarizes the main characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies provided data on mortality based on the specific vasopressor(s) administered [38,43,49,51]. The highest mortality rate was observed in patients treated with vasopressin or epinephrine (78% and 76%, respectively) [43].…”
Section: Resultsmentioning
confidence: 99%
“…A study of 31 ICU patients on norepinephrine found aerosolized milrinone did not have a positive impact on right ventricular (RV) function or afterload [ 16 ]. One retrospective study of 10 patients found adding angiotensin II reduced the norepinephrine equivalent dose by 30.4%; however, 50% of patients died after care was withdrawn and the other 50% of patients remained hospitalized [ 17 ]. In patients with severe or refractory septic shock, corticosteroids are recommended with consideration for dexamethasone or hydrocortisone as primary options (e.g., hydrocortisone 200 mg daily) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, plasma levels of DPP4, the entry receptor for MERS-CoV, were reported to be decreased in COVID-19 patients [ 285 ] and in patients infected with MERS-CoV [ 286 ]. Interestingly, in small cohorts of COVID-19 patients, Ang-II has been used to treat COVID-19-induced vasodilatory shock [ [287] , [288] , [289] ].…”
Section: The Roles Of Ace2 and Angiotensin II In Coronavirus-induced mentioning
confidence: 99%